Effectiveness of Acupuncture Therapy to Reduce Pain in Patients with Upper Trapezius Myofascial Pain Syndrome: A Meta-Analysis - Saraspuri, Niken Putri Eka; Tamtomo, Didik; Murti, Bhisma (Indonesian Journal of Medicine, 2022)
Background: Upper trapezius myofascial pain syndrome is a muscle pain condition associated with sensory, motoric, or autonomic functions and generated by trigger point arising from hardened and stiff taut band of muscle fiber while being touched as well as palpated. One of the interventions to reduce the pain is by using acupuncture therapy. The study aims to analyze and estimate the effectiveness magnitude of acupuncture therapy toward the pain reduction in patients with upper trapezius myofascial pain syndrome.Subjects and Method: This was a systematic review and meta-analysis study using PRISMA diagrams. The article search was conducted based on the eligibility criteria using the PICO Model. population: patients with upper trapezius myofascial pain syndrome. Intervention: acupuncture therapy. Comparison: placebo acupuncture. Outcome: reduced pain. The articles used were from 6 databases, namely Pubmed, Google Scholar, Science Direct, Scopus, Spinger Link, and Hindawi Key words for article search were “acupuncture” OR “acupuncture therapy” AND “upper trapezius pain” OR “upper trapezius myofascial pain syndrome” OR “upper trapezius MPS” AND “Randomized Con¬trolled Trial” OR “RCT”. Inclusion criteria used of the study were full text articles with Randomized Controlled Trial study design, measure of association used was Mean SD. Articles were analyzed using the Review Manager 5.3 application.Results: The 9 articles reviewed were from Taiwan, China, UK, Turkey, Brazil, and Iran. The study result indicated that acupuncture therapy was effective in reducing pain in upper trapezius myofascial pain syndrome. Upper trapezius myofascial pain syndrome that obtained acupuncture therapy had average score of pain -1.16 units lower than placebo acupuncture (SMD= -1.16; CI 95%= -1.93 to -0.39; p= 0.003).Conclusion: Acupuncture therapy was effective in reducing pain in upper trapezius myofascial pain syndrome.Keywords: acupuncture, pain, upper trapezius myofascial pain syndrome, randomized controlled trial, meta-analysis.Correspondence: Niken Putri Eka Saraspuri. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: nikenputri54@gmail.com. Mobile: 081327372766.Indonesian Journal of Medicine (2022), 07(03): 326-336https://doi.org/10.26911/theijmed.2022.07.03.09